Patrocinio de marcas y los Derechos de Imagen: qué está cambiando en el deporte universitario de Estados Unidos y el caso de Messi - Antequera, Ricardo E. (Pontificia Universidad Católica del Perú, 2025)
This study delves into how brand sponsorship and image rights are reshaping the sports industry, with a particular focus on Lionel Messi’s role in Inter Miami of the MLS. It examines the growing economic importance of image rights and the influence of legislative measures such as the Pelé Law and the NCAA v. Alston case on athletes’ image rights. Furthermore, it highlights the impact of NIL laws in U.S. college sports and the role of social media in athletes’ image monetization.

Este trabajo explora cómo el patrocinio de marcas y los derechos de imagen han cambiado la industria del deporte, especialmente a través del ejemplo de Lionel Messi en el Inter Miami de la MLS. Examina la importancia de estos derechos en la economía moderna y cómo la legislación como la Ley Pelé y el caso NCAA v. Alston están redefiniendo los derechos de imagen de los atletas. Además, aborda el impacto de las leyes NIL en el deporte universitario en EE. UU. y el papel de las redes sociales en la monetización de la imagen de los atletas.
Brand sponsorship and Image Rights: what is changing in university sports in the United States and the case of Messi
Keywords: Image rights; Brand sponsorship; Lionel Messi; College sports; NIL; Social media; Pelé Law; NCAA; Derechos de imagen; Patrocinio de marcas; Lionel Messi; Deporte universitario; NIL; Redes sociales; Ley Pelé; NCAA; https://purl.org/pe-repo/ocde/ford#5.05.00